2001
DOI: 10.1001/archinte.161.15.1814
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Pharmacotherapy of Obesity 2000

Abstract: To clarify the efficacy of antiobesity drugs, this article reviews all long-term (> or =36 weeks), placebo-controlled trials of obesity pharmacotherapy published since 1960. Since fears of anorexiant-induced heart valve damage preclude many physicians and patients from even considering antiobesity drugs, this area is also reviewed in-depth. Electronic database and manual bibliography search was used to identify all relevant publications. While existing studies are too few and heterogeneous to warrant meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
101
1
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(108 citation statements)
references
References 99 publications
1
101
1
5
Order By: Relevance
“…Although the association between overweight and intake of foods with high sugar and fat content and insufficient physical activity is well known,23 - 25 , 27 , 28 this was not observed in this study, probably because they represent widespread practice among the assessed schoolchildren, regardless of body weight. Moreover, the present study showed the association between some dietary habits (eating sweets and soft drinks ≥3 times/week, having lunch daily) and some behaviors of daily living (physical activity ≥3 times/week, free hours without energy expenditure) with gender, which could indicate the need for differentiated preventive interventions for boys and girls.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Although the association between overweight and intake of foods with high sugar and fat content and insufficient physical activity is well known,23 - 25 , 27 , 28 this was not observed in this study, probably because they represent widespread practice among the assessed schoolchildren, regardless of body weight. Moreover, the present study showed the association between some dietary habits (eating sweets and soft drinks ≥3 times/week, having lunch daily) and some behaviors of daily living (physical activity ≥3 times/week, free hours without energy expenditure) with gender, which could indicate the need for differentiated preventive interventions for boys and girls.…”
Section: Discussioncontrasting
confidence: 62%
“…But the lack of physical activity seems to have broader implications. Another recent study showed that sedentary children have reduced physical fitness, with a negative impact on flexibility, strength of several muscle groups and muscle explosion, which are even worse in obese and overweight children 28. Therefore, as physical fitness decreases, exercise intolerance increases, further promoting physical inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…It is a chronic metabolic disorder caused by an unhealthy lifestyle, eating behaviors and an imbalance between energy intake and expenditure. However, diet and physical exercise are usually not very effective, and most patients regain weight even after successful weight loss [1]. Obesity is a major social health problem in many developed countries, and a risk factor associated with the development of type II diabetes, coronary heart disease, hyperlipidemia, hypertension and metabolic syndromes [2,3], certain types of cancer and osteoarthritis [4].…”
Section: Introductionmentioning
confidence: 99%
“…2,19,20 Clinically important weight loss, defined by obesity experts as loss of 5-10% of baseline weight, [21][22][23][24] may improve lipid, glucose, and blood pressure levels, [25][26][27] with potential reductions in cardiovascular disease. [28][29][30] However, it is unclear if weight loss improves risk factors in all obese persons or only in high-risk groups. Finally, it is important to determine if weight loss studies are applicable to the everyday clinical management of obese patients.…”
Section: Introductionmentioning
confidence: 99%